2021
DOI: 10.1002/eco.2343
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trophic state responses of a large tropical coastal lagoon to land use changes and nutrient transport

Abstract: The watershed of a large tropical coastal lagoon, historically hosting large sugarcane crops, which has been reduced during the last decades. It suggests that land use and land cover changes (LULCC) would lower the trophic state of the coastal lagoon due to less fertilization application and consequently reducing nutrient transfer into the lagoon. In this context, this study assessed the influence of LULCC, represented by the reduction of the sugarcane crops on the trophic state of a large tropical coastal lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Past research has demonstrated that there can be a strong association between water quality and land use (de Mello et al, 2018; Zhang et al, 2020), including grassland, forest, bare lands, agricultural, industrial and urban land cover types (Ding et al, 2016; Zhang et al, 2020). The agricultural, industrial and urban land use strongly influences nutrient concentrations (N and P) and organic pollution in rivers (Campaneli et al, 2021). The excess application of inorganic fertilizers in agricultural areas along with soil erosion has resulted in the high loading of nutrients into water bodies (Bu et al, 2014; Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has demonstrated that there can be a strong association between water quality and land use (de Mello et al, 2018; Zhang et al, 2020), including grassland, forest, bare lands, agricultural, industrial and urban land cover types (Ding et al, 2016; Zhang et al, 2020). The agricultural, industrial and urban land use strongly influences nutrient concentrations (N and P) and organic pollution in rivers (Campaneli et al, 2021). The excess application of inorganic fertilizers in agricultural areas along with soil erosion has resulted in the high loading of nutrients into water bodies (Bu et al, 2014; Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%